(untitled) (Revista Contexto & Saúde, 2023)
Introduction: Self-medication is a reality for a large portion of the population. Although directly related to this practice, the pharmacy attendant is not considered in studies that evaluate self-medication in Brazil. Very little is known about the knowledge of pharmacy attendants concerning the risks of self-medication. Objective: The present study aims to evaluate the use of self-medication by pharmacy attendants in Pelotas, Rio Grande do Sul, in addition to their knowledge about the risks involved in this practice. Method: A cross-sectional study was carried out on pharmacy attendants of private pharmacies in Pelotas. Results: 41,6% of the pharmacy attendants stated that self-medicated, at last, once a month. 66,3% declare that recommend over-the-counter medication to customers. 30,7% of the participants stated that trey already have been encouraged to indicate medicines, however, 75,2% do not consider themselves prepared to help clients with self-medications. Conclusion: Self-medication and assistance with self-medication of patients is a common practice among pharmacy attendants. Therefore, it is up to the pharmacist to assume responsibility for professionals to minimize the risks of self-medication for training and attendants.